Peranan Gender dalam Usaha Tani di Kawasan Indonesia Bagian Timur - Notoatmojo, Budiman (Bina Nusantara University, 2001)
The role of gender is dominant in agriculture development and income, especially the role of the housewife. They are dominant in house duties, controlling the financial, children’s education, village or farm events, and increase the income for their families. The research’s aims are to determined the role of gender in the household, farming, project activities in doing rural activities, and in increasing farmer’s income based on the research done in North Sulawesi, South Sulawesi, and Gorontalo. It can be concluded that the housewife’s role in doing daily chores, decising, farming activities, doing farming activities, joining rural activities, and increasing the family income are more dominant than male.